El registro fotográfico de murales prehispánicos en México - Alvarado-Tapia, Ricardo Alvarado Tapia (2012)
From more than two decades of experience shooting prehispanic murals in the project La pintura mural prehispánica en México, UNAM and research on the topic roll in my Master’s thesis, we present some results and problems that have to register those murals. These reproductions are made to protect, conserve, study and communication to society and future generations the patrimonial works or the images and information relating to them.